2019
DOI: 10.2106/jbjs.18.00632
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Serum, Synovial, and Tissue Testing for Chronic Periprosthetic Joint Infection After Hip and Knee Replacements

Abstract: Background: Chronic periprosthetic joint infection (PJI) is a devastating complication that can occur following total joint replacement. Patients with chronic PJI report a substantially lower quality of life and face a higher risk of short-term mortality. Establishing a diagnosis of chronic PJI is challenging because of conflicting guidelines, numerous tests, and limited evidence. Delays in diagnosing PJI are associated with poorer outcomes and morbid revision surgery. The purpose of this systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 241 publications
2
59
1
12
Order By: Relevance
“…This is the first systematic review and meta-analysis about the utility of D-dimer for the diagnosis of PJI. We found that D-dimer has limited performance for the diagnosis of PJI, with a pooled sensitivity and specificity of 0.82 and 0.70, respectively, and had a poorer diagnostic value than that of CPR and ESR reported by Carli AV et al [31]. In this systematic review, the pooled sensitivity and specificity of CRP were 0.85 and 0.81, respectively, and the pooled sensitivity and specificity of ESR were 0.82 and 0.79.…”
Section: Discussioncontrasting
confidence: 62%
“…This is the first systematic review and meta-analysis about the utility of D-dimer for the diagnosis of PJI. We found that D-dimer has limited performance for the diagnosis of PJI, with a pooled sensitivity and specificity of 0.82 and 0.70, respectively, and had a poorer diagnostic value than that of CPR and ESR reported by Carli AV et al [31]. In this systematic review, the pooled sensitivity and specificity of CRP were 0.85 and 0.81, respectively, and the pooled sensitivity and specificity of ESR were 0.82 and 0.79.…”
Section: Discussioncontrasting
confidence: 62%
“…• This is a key step in diagnosis; Erythrocyte sedimentation rate (ESR) and c-reactive protein (CRP) are routinely available, cheap, and provide rapid results • Based on a recent systematic review, ESR has a sensitivity of 82% and a specificity of 79%, whilst CRP has a sensitivity of 85% and a specificity of 81% [4]. CRP and ESR may not be raised in low virulence PJI [5] • A threshold of ESR > 30 mm/h and CRP > 10 mg/L is recommended for chronic PJI [1] • Plasma viscosity with a threshold of >1.81 mPa•s may also be used with a specificity of 94% and sensitivity of 58% [6] 4.…”
Section: Blood Testsmentioning
confidence: 99%
“…• SF culture has been shown to have a pooled sensitivity of 69% and specificity of 96% [4]. Cultures should be maintained for five to seven days, or up to 21 days if there is suspicion of low-virulence organisms.…”
Section: Microbiological Culture Of Synovial Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…), joint uid indicators (percentage of neutrophils, c-reactive protein, c-defensin, etc.) and tissue cultures [3,9,16]. The methods used to evaluate functional recovery include an early postoperative range of motion (ROM) measurement, a quadriceps muscle strength measurement, the sit to stand test, the 6-minute walking test [18], and a psychological assessment [7].…”
Section: Introductionmentioning
confidence: 99%